(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
This article addresses the gaps in historical narratives of dance in Chile, which tend to omit modern dance expressions prior to 1940. Based on the notion of revisiting this history, it proposes a methodological approach based on photographic analysis and reenactment practices from a post-custodial archive perspective. Through the study of a 1935 photograph of Elsa Martin by Ignacio Hochhäusler and the work in Proyecto Desenfoque, it shows how the body in motion acts as a living archive (Practice as Research). This practice allows challenging documentary absences, decentering the hegemonic narrative, and making visible the movements that preceded the institutionalization of dance in Chile.